Pengaruh Penambahan Tepung Daging Bekicot (Achatina Fulica) dalam Pembuatan Mie Basah Terhadap Komposisi Proksimat dan Daya Terima - Cahyaningrum, Nindya Martha, Pramudya Kurnia, STP, M.Agr, Rusdin Rauf, S.TP., M.P (2013)
Background : Processing wet noodles can be done by mixing flour and other flour. Snail meat flour used as addition of wheat flour because it contains higher of animal protein than chicken egg protein that is 15,8%. Purpose : The purpose of this study is to evaluate the effect of snail meat flour as an addition in the making of wet noodles on proximate composition and acceptability. Methods : The study design used was completely randomize designed that uses four additional variations (0%, 5%, 10% and 15%). Data proximate composition and acceptance analyzed using statistical one way ANOVA test and followed DMRT (Duncan's Multiple Range Test) with a level of 5%. Results : Result of this study indicates that there is significant effect of adding flour to the snail meat on protein content and fat content wet noodle. The more the additional of the snail meat meal increased levels of protein and fat content of the resulting wet noodle. There was no effect of snail meat flour addition to the ash content and moisture content of wet noodle. Carbohydrate levels were highest in the wet noodles by addition of snail meat flour 0% that is 49,03% and lowest carbohydrate levels on a wet noodle with the addition of snail meat flour 10% that is 25,8%. There was effect of snail meat flour addition on acceptance level of a wet noodle. Based on color, aroma, taste, texture and overall acceptance panelists favored addition was on the addition of red bean flour is 0% and 5%. Conclusion : There is the effect of adding flour to the snail meat protein content and fat content wet noodle. There was no effect of snail meat flour addition to the ash content and moisture content of wet noodle. Carbohydrate levels were highest in the wet noodles by addition of snail meat flour 0% that is 49,03% and lowest carbohydrate levels on a wet noodle with the addition of snail meat flour 10% that is 25,8%. There was effect of snail meat flour addition on acceptance level of a wet noodle. Suggestion : The making of wet noodles can use addition of snail meat flour of 5%.